The Psychogeographic Fotoromanzo as an Urban Affective Mapping Practice: Notes on Ralph Rumney’s The leaning Tower of Venice - Elisa Mozzelin (European Journal of Creative Practices in Cities and Landscapes)
Psychogeography, a method of reality analysis incubated in the 1950s by the Situationist International, was presented early on as a methodology capable of unraveling the precise effects of the geographic environment on the psychic behavior of individuals, paving the way for a dialogue between geography and psychology. Ralph Rumney, drawing from the Situationist lesson, translates his research on the city of Venice into a narrative form, choosing the fotoromanzo as an innovative form of representation. Retaining the peculiarities of this type of narrative, Rumney aims at rendering the analysis of the city of Venice into a topographical condensate of affective mapping, drawing from the subversive potential of the psychogeographic method.